THE ROLE OF SOCIAL MEDIA IN INCREASING RURAL GENERATION Z PARTICIPATION IN THE 2024 ELECTIONS : A STUDY IN SUNGAI ANA VILLAGE, SINTANG DISTRICT: PERAN MEDIA SOSIAL DALAM MENINGKATKAN PARTISIPASI GENERASI Z DI PEDESAAN PADA PEMILU TAHUN 2024 SUATU STUDI DI DESA SUNGAI ANA KECAMATAN SINTANG - Zainudin, Abang (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
This research investigates the role of social media in increasing the political participation ofGeneration Z in rural areas, especially Sungai Ana Village, Sintang District during the 2024 GeneralElection. Using a mixed methods approach, this research combines a literature review, survey, in-depthinterviews, social media content analysis, and observation participatory to collect comprehensive data.These findings reveal that social media platforms such as Instagram, TikTok, and WhatsApp are veryimportant for increasing political awareness among Generation Z users in Sungai Ana Village, SintangDistrict. About 91% of respondents rely on social media as their main source of political information, andadmit that these platforms help them better understand political issues and candidates. These findingshighlight the need for increased media literacy and critical thinking skills to combat the spread of fake news.The study concludes with recommendations for policymakers and stakeholders, emphasizing the importanceof improving internet infrastructure in rural areas, promoting educational campaigns on media literacy,and fostering collaboration between governments, educational institutions, and social media platforms todevelop effective political education initiatives. By overcoming these challenges and harnessing thepotential of social media, Generation Z's political engagement in rural areas, especially in Sungai AnaVillage, can be significantly increased, resulting in more active and informed participation in thedemocratic process